2021
DOI: 10.5435/jaaosglobal-d-21-00018
|View full text |Cite
|
Sign up to set email alerts
|

The Fragility of Statistical Findings in Achilles Tendon Injury Research: A Systematic Review

Abstract: Introduction: Probability analysis with the reporting of P values is often used to determine the statistical significance of study findings in the Achilles literature. The purpose of this study was to determine the utility of applying a fragility analysis to comparative trials evaluating Achilles tendon injuries. Methods: We identified all dichotomous outcome data for comparative studies of Achilles tendon injuries published in 11 orthopaedic journals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 31 publications
4
11
0
Order By: Relevance
“…These values are consistent with the current orthopaedic literature reporting an average median FI of 3.81 1014,17,18,21,23,29 31,36,38,42,47 53,55 57 and FQ of 0.048. 1012,18,21,…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These values are consistent with the current orthopaedic literature reporting an average median FI of 3.81 1014,17,18,21,23,29 31,36,38,42,47 53,55 57 and FQ of 0.048. 1012,18,21,…”
Section: Discussionsupporting
confidence: 92%
“…For the outcomes included in this analysis, the median FI was 2.5 (IQR 2-4), the mean FI was 2.9 (±1.58), the median FQ was 0.032 (IQR 0.012-0.069), and the mean FQ was 0.049 (±0.062). These values are consistent with the current orthopaedic literature reporting an average median FI of 3.81 [10][11][12][13][14]17,18,21,23,[29][30][31]36,38,42,[47][48][49][50][51][52][53][55][56][57] and FQ of 0.048. [10][11][12]18,21,23,31,[47][48][49][50][51]53 The hypothesis of this study was confirmed, with more than half (78%) of outcomes analyzed having a loss to follow-up greater than the fragility index for that outcome.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These values are on par with prior studies assessing statistical fragility in the orthopaedic literature. 11 , 13 , 14 , 23 , 24 , 29 , 31 , 32 , 34 Most pertinently, Parisien et al 31 evaluated the statistical fragility of unspecified comparative trials for Achilles tendon pathology, presenting an overall FI of 4 and associated FQ of 0.048 for 51 outcome events. Parisien et al 32 further studied the statistical fragility of PRP utilization in rotator cuff repair and found an overall FI of 4 and FQ of 0.092 for 177 outcome events.…”
Section: Discussionmentioning
confidence: 99%